2022
DOI: 10.17219/acem/152942
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of St. John’s wort extract in depression therapy compared to SSRIs in adults: A meta-analysis of randomized clinical trials

Abstract: The efficacy and safety of St. John's wort extract in depression therapy compared to SSRIs in adults: A meta-analysis of randomized clinical trials [published online as ahead of print on October 11, 2022].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Furthermore, the link between air pollution and the pathogenesis of depression has been proven [ 53 ]. Novel therapeutics for neuropsychiatric conditions are under extensive study [ 54 , 55 ].…”
mentioning
confidence: 99%
“…Furthermore, the link between air pollution and the pathogenesis of depression has been proven [ 53 ]. Novel therapeutics for neuropsychiatric conditions are under extensive study [ 54 , 55 ].…”
mentioning
confidence: 99%
“…This review also offers novel insights into the role of specific modes and intensities of exercise in alleviating depressive symptoms, providing valuable information for future investigations. However, the consideration of exercise interventions as clinical treatments for mental disorders such as depression requires more rigorous randomized controlled trials to evaluate the efficacy of exercise interventions in treating depression [148][149][150][151]. While the effects of different types, intensities, frequencies, and durations of exercise on depression have been studied, further research is needed to determine the optimal exercise regimen for individuals with depression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a meta-analysis of clinical trials performed by Linde and colleagues in 2008 indicated Hypericum perforatum extract to be superior to a placebo in patients with major depression, to be similarly effective, and to have fewer side effects than standard antidepressants [ 91 ]. Thus, the volume of clinical research and meta-analytic data [ 69 , 71 , 88 ] reinforces the fact that Hypericum perforatum is the most studied, probably safe and effective adaptogenic herbal extract that might be recommended to practitioners as part of an integral clinical treatment to reduce depressive symptoms. Nevertheless, more research is warranted to evaluate factors that influence response to treatment, such as the type of extract, the duration of the disorder and age of the participants, among others.…”
Section: Discussionmentioning
confidence: 99%